Frequency of Peripheral Neuropathy in Diabetic Patients with and Without Anemia: An Analytical Comparative Cross-Sectional Study - Farhat Ullah Bakhsh; Shamaila Burney (Pakistan Journal of Clinical Research, 2026)
Background: Diabetic peripheral neuropathy (DPN) is a common complication of diabetes, causing sensory loss, pain, gait impairment, ulcers, and amputation. Its substantial burden in Pakistan warrants systematic screening, while anemia and vitamin B12 deficiency may further contribute to neuropathic clinical manifestations. To evaluate the DPN frequency in patients with and without anemia in diabetic patients to determine the independent predictors. Methods: 192 adults type 2 diabetes were studied using an analytic comparative cross-sectional framework, consisting of equal representation of anemia and non-anemia groups. A standardized examination based on the Michigan Neuropathy Screening Instrument was used to make the assessment of DPN. There was a group comparison, estimates of effects and multivariate logistic regression. Results: DPN was present in 92/192 (47.9%; 95% CI 40.7-55.2). Neuropathy occurred in 58/96 (60.4%) participants with anemia versus 34/96 (35.4%) without anemia (p